Dimensions of Qur'anic Exegesis in the Repetition of Surah Al-Qamar Verses 17, 22, 32, And 40: A Perspective from Ibn Kathir's Tafsir - Ahmad Zaky Ramadhan (Global Writing Academica Researching and Publishing, 2026)
The repetition of Qur'anic verses (takrār al-ayat) is one of the distinctive rhetorical features of the Qur'an, reflecting profound meanings, wisdom, and communicative purposes. One of the most significant examples appears in Surah Al-Qamar verses 17, 22, 32, and 40 through the repeated statement,